TINJAUAN PELAKSANAAN RAPAT ANGGOTA TAHUNAN (RAT) PADA KOPERASI DI KECAMATAN BONDOWOSO - Amanda Puspita Sari; Shilfi Diana Putri; Wardatul Hasanah; Nurul Setianingrum (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
One of the main tenets that all teachers must adhere to is to have at least one student volunteer each year for that minimum period of one year. It is a single aspect of a company's work environment over a certain period of time. The type of research used is qualitative descriptive research, or research whose main aim is to understand and understand the types of joint work that are and are not carried out in Bondowoso Province, as well as the reasons why joint work is not carried out. finished there. In order to obtain complete data regarding requests for Annual Meetings in Bondowoso Province